Неформальна освіта дорослих у США у колоніальний період - Терьохіна, Наталія (Studies in Comparative Education, 2014)
У статті досліджено витоки становлення неформальної освіти дорослих у Сполучених Штатах Америки; виявлено провідні чинники розвитку неформальної освіти дорослих; наведено приклади неформальної освіти дорослих у XVII–XVIII ст. у США, висвітлено її основні характеристики. Доведено, що освіта дорослих є найдавнішим видом освіти у Сполучених Штатах. Вона виникла переважно як позаінституційна форма освіти й розвивалася протягом чотирьох століть. Виявлено, що у колоніальний період переважною формою освіти дорослих була неформальна освіта. Закладами неформальної освіти дорослих досліджуваного періоду слугували таверни, кав'ярні, бібліотеки, громадські лекції, вечірні школи, добровільні товариства за інтересами, які стали підґрунтям для створення організацій більш масового характеру. В статье исследуются истоки становления неформального образования взрослых в Соединенных Штатах Америки; определяются ведущие факторы развития неформального образования взрослых; приведены примеры неформального образования взрослых в XVII–XVIII вв. в США, освещены его основные характеристики. Доказано, что образование взрослых является древнейшим видом образования в Соединенных Штатах. Оно возникло преимущественно как неинституционная форма образования и развивалось на протяжении четырех веков. Доказано, что в колониальный период преобладающей формой образования взрослых было неформальное образование. Учреждениями неформального образования взрослых исследуемого периода служили таверны, кофейни, библиотеки, общественные лекции, вечерние школы, добровольные общества по интересам, которые стали основой для создания организаций более массового характера. Adult education is the oldest sphere of education in the United States. It emerged primarily as non-institutional form of education more than four centuries ago. In the colonial period the dominant form of adult education was non-formal education. The origins of the formation of non-formal adult education in the United States of America are explored in the article, its major facts and characteristics are explained; the examples of non-formal adult education in the colonial period are found. Much of adult education in the early colonial period owed less to formal institution than to everyday living. Many factors affected access to learning opportunities. The thirteen colonies remained very much a part of the transatlantic community, within which informal learning opportunities flourished especially in the areas of business and daily life for the literate: correspondence network, an ever growing selection of both domestic and imported literature, and community activities influenced by world travelers. Colonial seaport taverns and coffee houses also played an educational as well as a social role. Taverns stored newspapers, made public announcements, hosted clubs meetings and dances, held public readings and theatrical entertainment. Political groups found these gathering places to be useful for influencing public opinion: it was in these «schools for people» that information was exchanged, opinions heard and debated, and contacts often established with a wider world. Lectures in particular served the male and female members of «polite society», and a lecture circuit developed on the Eastern seaboard. The lectures might be supplemented by a printed syllabus, illustrations, demonstrations. Parish libraries reached a wider public, sometimes even Native Americans and African Americans. The «mutual improvement» principle was evident in the voluntary societies that were initially an elite phenomenon, but which laid a foundation for more popular agencies. Apprenticeship was the most pervasive form of adult education. It provided for technical competence; moral and religious instruction; and some reading, writing, and arithmetic. Its opportunities tended to be segregated in terms of gender, class, and race. Evening schools proliferated in the seventeenth century, serving apprentices entitled to free instruction as well as men and women able to pay modest fees. The curriculum met liberal, vocational, and leisure interests. The scope and potential of Apprenticeship and evening schools for expanding access to learning, including access for women and minorities, was significant. Informal education in the colonial period influenced the literate and the illiterate, the prosperous and the poor, the free and the enslaved.